Community exposure to hazardous site remediation in rural New Zealand: an exposed‐referent study of serum dioxins and health effects - David McBride; Kirsten Lovelock; Daniel Shepherd; Kim Dirks; David Welch; Andrew Gray (Elsevier, 2016)
Abstract Objective: The New Zealand Ministry of Health responded to community concern about dioxin exposure during on‐site remediation of a pesticide‐contaminated rural area by commissioning this exposed‐referent study of serum dioxins and health in local residents. Methods: All 200 residents were eligible, with age and sex matching to demographically comparable referents. Face‐to‐face interviews included questions on health status, health‐related quality of life (HRQOL) and perceptions about community consultation. Thirty serum samples were obtained, eligibility being based on likelihood of exposure and age. Both HRQOL and serum outcomes were analysed by the appropriate regression methods. Results: Of 200 eligible residents, 139 (69.5%) participated, with 139 matched referents. Mapua residents had lower physical and psychological HRQOL scores, but no difference in health status. 2,3,7,8 TCDD was below the limit of detection in the majority of all serum samples, with some congeners being higher in referents. Perceptions of the communication process were equivocal. Conclusions: Both dioxin levels and measures of health did not differ significantly between the exposed community and controls. Implications for public health: The results suggest neither significant dioxin exposure nor community health effects. Oversight by expert panel with health expertise, allied to sound communication, may have helped the community understand the risks.